2013
DOI: 10.1128/mcb.00469-13
|View full text |Cite
|
Sign up to set email alerts
|

Pdx-1 Activates Islet α- and β-Cell Proliferation via a Mechanism Regulated by Transient Receptor Potential Cation Channels 3 and 6 and Extracellular Signal-Regulated Kinases 1 and 2

Abstract: The homeodomain transcription factor Pdx-1 has important roles in pancreatic development and ␤-cell function and survival. In the present study, we demonstrate that adenovirus-mediated overexpression of Pdx-1 in rat or human islets also stimulates cell replication. Moreover, cooverexpression of Pdx-1 with another homeodomain transcription factor, Nkx6.1, has an additive effect on proliferation compared to either factor alone, implying discrete activating mechanisms. Consistent with this, Nkx6.1 stimulates main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 60 publications
8
61
0
Order By: Relevance
“…For gene overexpression studies, cytomegalovirus (CMV) promoter-driven recombinant adenoviruses containing mouse Pdx-1 (AdCMV-mPdx-1), bacterial ␤-galactosidase (AdCMV-␤-Gal), or green fluorescent protein (GFP; AdCMV-GFP) were constructed and used as described previously (8,9,13). We constructed CMV promoter-driven adenoviruses containing human Pdx-1 (hPdx-1), rat Noggin, rat Bmp3, rat Fstl5, and rat Inhbb by cloning the cDNA constructs into a pAdTrack shuttle vector and using the Ad-Easy system to generate the recombinant adenoviruses, as previously described (14).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For gene overexpression studies, cytomegalovirus (CMV) promoter-driven recombinant adenoviruses containing mouse Pdx-1 (AdCMV-mPdx-1), bacterial ␤-galactosidase (AdCMV-␤-Gal), or green fluorescent protein (GFP; AdCMV-GFP) were constructed and used as described previously (8,9,13). We constructed CMV promoter-driven adenoviruses containing human Pdx-1 (hPdx-1), rat Noggin, rat Bmp3, rat Fstl5, and rat Inhbb by cloning the cDNA constructs into a pAdTrack shuttle vector and using the Ad-Easy system to generate the recombinant adenoviruses, as previously described (14).…”
Section: Methodsmentioning
confidence: 99%
“…Our laboratory has demonstrated that Pdx-1 and Nkx6.1, two homeobox domain transcription factors well known for key roles in islet ␤-cell development, activate proliferation when overexpressed in rat or human islets while maintaining and enhancing GSIS, respectively (7)(8)(9)(10). Importantly, the increase in proliferation induced by either factor has little to no impact on ␥-H2AX expression, suggesting that these factors engage "safe" pathways of islet cell replication.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[ [81][82][83][84][85][86][87][88][89] Ngn-3 Promotes ectopic development of beta and delta cells.Associated with beta cell neogenesis and exocrine to endocrinal conversion.…”
Section: Transcription Factorsmentioning
confidence: 99%